Involvement of DNA polymerase μ in the repair of a specific subset of DNA double-strand breaks in mammalian cells - Capp, Jean-Pascal (Oxford University Press, 2007)
The repair of DNA double-strand breaks (DSB) requires processing of the broken ends to complete the ligation process. Recently, it has been shown that DNA polymerase μ (polμ) and DNA polymerase λ (polλ) are both involved in such processing during non-homologous end joining in vitro. However, no phenotype was observed in animal models defective for either polμ and/or polλ. Such observations could result from a functional redundancy shared by the X family of DNA polymerases. To avoid such redundancy and to clarify the role of polμ in the end joining process, we generated cells over-expressing the wild type as well as an inactive form of polμ (polμD). We observed that cell sensitivity to ionizing radiation (IR) was increased when either polμ or polμD was over-expressed. However, the genetic instability in response to IR increased only in cells expressing polμD. Moreover, analysis of intrachromosomal repair of the I-SceI-induced DNA DSB, did not reveal any effect of either polμ or polμD expression on the efficiency of ligation of both cohesive and partially complementary ends. Finally, the sequences of the repaired ends were specifically affected when polμ or polμD was over-expressed, supporting the hypothesis that polμ could be involved in the repair of a DSB subset when resolution of junctions requires some gap filling.